A rare case report of intermediate osteopetrosis and review of literature - Priyanka Verma; Sonali Kadam; Hemant Rangnath Umarji; Varun Surya (Wolters Kluwer Medknow Publications, 2014)
Osteopetrosis also known as "marble bone disease" is a group of rare genetic disorders caused by osteoclast failure, which ranges widely in severity. Osteopetrosis presents with a spectrum of craniofacial abnormalities such as frontal bossing, macrocephaly, hydrocephaly, and cranial hyperostosis. Osteopetrosis is caused by failure of osteoclast development or function and mutations in at least 10 genes have been identified as causative in humans, accounting for 70% of all cases. These conditions can be inherited as autosomal recessive, dominant or X-linked traits with the most severe forms being autosomal recessive. We present a rare case of osteopetrosis in a 10-year-old boy who reported with an unhealed socket after tooth extraction. The characteristic clinical and radiographic findings were suggestive of intermediate osteopetrosis.